Development of a liquid chromatography method for the analysis of oil extract of artemisia cina - S. K. Ordabayeva; A. D. Serikbayeva; H. S. Farshad; G. Bakhytkyzy (Разработка и регистрация лекарственных средств)
Introduction. The problem of development and implementation of own drugs in Kazakhstan today is acute and urgent. The solution to this problem is possible through the use of own resources – domestic medicinal plant raw materials. A promising medicinal raw material is Artemisia cina – an endemic medicinal plant of the of the Turkestan region of Kazakhstan.Aim. Designing a liquid chromatography methodology to analyze the oil extract obtained from Artemisia cina.Materials and methods. Standard sample (SS) of santonin, Artemisia cina’s oil extract. The substance was identified and quantitatively determined using an Agilent Technologies 1200 liquid chromatograph (USA) equipped with ChemStation software.Results and discussion. The main active substance of the oil extract was analyzed using high-performance liquid chromatography (HPLC) method. Choosing the separation conditions for the column involves determining the best composition of the mobile phase and the rate of elution. There were used a reversed-phase system with sorbent C18 and a mobile phase consisting of acetonitrile and a phosphate buffer with a pH of 6.8. Chromatographic studies of the substance were carried out in a gradient mode at an analytical wavelength of 237 nm. The retention time of the standard sample (SS) of santonin matched the retention time (tR) of santonin isolated from the oil extract of Artemisia cina and amounted to 14.3 minutes.Conclusion. A liquid chromatography method has been established for the identification and quantitative determination of the oil extract, focusing on the main active substance, santonin.